analysis the effective factors on the formation of women\'s ideal territory in urban parks (Case study: El Goli, shams , valiasr of Tabriz) - sara ghahri lalaklou; rasool darskhan; mahsa faramarzi asli; morteza mirgholami; samad sabbagh dehkharghani (تحقیقات کاربردی علوم جغرافیایی)
Urban design that the first was paying attention to the aesthetic dimension,now pays to the quality of the public territory in terms of physical social cultural and creating places for people using.the public territory is a temporary territory and everyone has access to and has the right to use it.tendency to have a territory and defend of  it, is intrinsic.since now women like men are present in society but they do not have enough power to choose their territory so this research is trying to introduce the effective items to creating ideal territory.the data of this study is descriptive-analytical/survey.type of study is quantitative and qualitative. The study is field and library based.the statistical population includes women with different cultures ages behaviors in ealgoli park,women's shams park,valiasr park of Tabriz that the woman were randomly selected.the sample size is 384 and it based on the Cochran formula. At first at the descriptive level were investigated with subject statistics indicators and then at the inferential level used of exploratory factor analysis to determine the model.the results include 5 influential components.these components are landscape-functional-security-morphology-psychological.